Sobre: El tiempo de la improvisación, de Alberto Giordano. Rosario: Iván Rosado, 2019. - Grossi, Bruno (Universidad Nacional del Litoral, 2019)
Sobre: El tiempo de la improvisación, de Alberto Giordano. Rosario: Iván Rosado, 2019.